3 | ( | x | + | 2 | ) | ÷ | 5 | = | ( | x | + | 2 | ) |
方程左边 = | 3 5 | ( | x | + | 2 | ) |
3 5 | ( | x | + | 2 | ) | = | ( | x | + | 2 | ) |
方程左边 = | 3 5 | x | + | 3 5 | × | 2 |
= | 3 5 | x | + | 6 5 |
3 5 | x | + | 6 5 | = | ( | x | + | 2 | ) |
方程右边 = | x | + | 2 |
3 5 | x | + | 6 5 | = | x | + | 2 |
3 5 | x | − | x | = | 2 | − | 6 5 |
- | 2 5 | x | = | 2 | − | 6 5 |
- | 2 5 | x | = | 4 5 |
- | 4 5 | = | 2 5 | x |
2 5 | x | = | - | 4 5 |
x | = | - | 4 5 | ÷ | 2 5 |
= | - | 4 5 | × | 5 2 |
= | - | 2 | × | 1 |
x | = | - | 2 |